The industrial rise of the Third Italy: Open windows of locational opportunity? - Ron Boschma (European Regional Science Association (ERSA), 1998)
The article aims to test a theoretical concept (the Window of Locational Opportunity concept) which provides a particular perspective with respect to the key problem in economic geography of how to explain the ability of regions to generate or apply new technology. In short, this WLO-concept holds the view that windows of locational opportunity tend to open up in the event of new techno-industrial development: these are likely to provide opportunities of industrial development for both leading and backward regions. This is because the impact of space may be unpredictable and rather weak for several reasons: there is likely to be a poor match with the new requirements of new techno-industrial activities, their creative ability may safeguard their development in unfavourable places, while local conditions favourable to their development are likely to be of a generic nature. Following the principles behind this theoretical concept, we present a long-term spatial analysis of Italy, which aims to explain the industrial rise of the Third Italy region in the post-war period. It attempts to assess empirically the impact of spatial conditions (including culture) on the industrial rise of the so-called Third Italy region during its initial stage of development in the 1950s and 1960s. A regression technique has been used to determine which of many potential factors (for instance, culture, industrial specialization, infrastructure and low-cost, flexible labour) in the 1950s could be held responsible for the particular type of industrial development in the Third Italy area, which was based on dense networks of flexible, strongly related, small and medium-sized firms in craft-based industries (clothing, ceramics) in a number of specialized industrial districts. By doing so, we focus attention on the extent to which the industrial rise of the Third Italy region was a rather accidental event that could also have occurred in other regions such as the First Italy (the industrial heartland of the North) and the Second Italy (the backward South). The preliminary results at this stage of the analysis tend to point out that the cultural dimension makes the difference: this particular type of industrial development took place in the Third Italy region because of a local culture of entrepreneurship and cooperation which seems to be lacking to some degree in the other regions in Italy.
Keywords: 330